Electrical Modelling and Power Quality Analysis of Three-Phase Induction Furnace - Moreira, Alexandre C.; Silva, Luiz C. P. da; Morales Paredes, Helmo K. [UNESP]; IEEE (Ieee, 2014)
The induction furnaces are loads having high power and nonlinear characteristic. The power consumption depends on the stage of melting metal in its interior and can cause serious problems on the electric power distribution systems, such as voltage fluctuations, voltage sags, current harmonics and voltage distortion. Thus, this paper presents the modeling and computational simulation of a six-pulse induction furnace, in order to contribute in power quality studies and connection disturbing loads in electrical power systems. The model of the induction furnace was implemented in PSIM software and used for analysis and evaluation of the potential impacts due to the connection of the induction furnace on the electrical power system, as well as the power quality. Furthermore, an analysis of the power quantities of IEEE 1459 standard are presented.
Keywords: Disturbing Load; Harmonic Distortion; Induction Furnace; Power Quality; Modeling; STD 1459-2010